Peran Komitmen Orgnisasi Sebagai Variabel Intervening Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai - Sabtohadi, Joko (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:This study aims to examine the direct and indirect effects of organizational culture on employee performance. This research is a quantitative study using primary data collected by survey techniques. The respondents of this study were 56 employees in the Regional Research and Development Agency of the Kutai Kartanegara. Data analysis using the Structural Equation Model based on Partial Least Square (SEM-PLS). The results showed that there was a significant direct effect of organizational culture on employee performance, organizational culture on organizational commitment, and organizational commitment on employee performance. The results also show that organizational commitment acts as a partial mediator of the organizational culture's relationship to employee performance. Keywords: Organizational Culture, Organizational Commitment, Employee Performance